Futsal training based on mini game situation: Effects on mastery of athlete techniques - Rohman Hidayat; Ayu Rizky Febriani; Arfin Deri Listiandi; Rifqi Festiawan; Moch Fath Khurrohman (UIR Press, 2022)
The aim of the study is to identify the influence of providing mini game situation and full game session training methods at the level of youth players' futsal playing skills. This is experimental study with 30 youth futsal athletes of Banyumas Regency (Age= M 16.2 ± SD 0.761), divided into two experimental groups design. Futsal skill instruments are used to analyze the mastery of an athlete's technique as measured by the speed of time in completing a task. The variables analyzed relate to the main techniques in the game of futsal: passing, controlling, dribbling, and shooting. In this regard, the results showed that the value obtained from the mini game situation exercise is higher than the full game session and a significant difference is found in the results of both exercises (M ± 47.00; p = 0.012), while the value of the influence of full game session (M ± 49.00 ; p = 0.003). It is seen that more complex practice patterns will improve the player's skills progressively. Overall, these findings suggest that coaches need to take into account the effective use of exercise to support the improvement of futsal skills in adolescent athletes.